Gender Differences in the Effect of Facial Attractiveness on Perception of Time - Tian, Yu; Li, Lingjing; Yin, Huazhan; Huang, Xiting (Frontiers in Psychology, 2019)
Perception of time plays a fundamental role in human social activities, and it can be influenced in social situations by various factors, including facial attractiveness. However, in the eyes of observers of different genders, the attractiveness of a face varies. The current study aimed to explore whether gender modulates the effect of facial attractiveness on perception of time. To account for individual differences in aesthetic standards, the critical stimuli presented to each participant were selected from an image pool based on the participant’s own attractiveness judgments. Using a temporal reproduction task, we measured the perception of time by men and women during viewing of faces of different attractiveness and gender. The results show that attractive opposite-sex faces elicited longer reproduced durations in men than unattractive opposite-sex faces, while facial attractiveness did not affect men’s reproduced durations in the case of same-sex faces. Conversely, women exhibited longer reproduced durations for attractive faces than for unattractive faces, regardless of facial gender. These results suggest that gender difference plays an important role in the effect of facial attractiveness on time perception.